Analysis Transtibial Patient’s Level of Knowledge in Maintaining the Health of the Stump in Prosthetics and Orthotics Clinic - Lestari, Firdha Alwani; Fauziah, Syifa; Adyas, Atikah (Journal of Prosthetics Orthotics and Science Technology, 2022)
Below the knee amputation (transtibial) is the most common amputation (Vitriana, 2002). Prosthesis is a device that has a function to replace part of the body after amputation. Prosthesis is aimed to help patients in daily activities, especially walking. After giving the prosthesis, the patient is given an explanation of how to wash the stump and prosthesis correctly. Prosthetist also suggested that prosthesis should be washed every day when not being used. Based on the data of Prosthetic and Orthotic clinics report in 2013, the majority of patient knowledge in maintaining health of stump is still limited. It’s shown with stump condition and prosthesis poor hygiene during the monitoring process. This study aimed to analyze the knowledge of patients transtibial amputation in maintaining stump health in Prosthetic and Orthotic Clinic Polytechnic Jakarta I. This study aimed to analyze the knowledge of patients transtibial amputation stump in maintaining health Prosthetic and Orthotic Clinic Polytechnic Jakarta I. There were 10 respondents who came to Prosthetics and Orthotics Clinic Polytechnic Jakarta I in June 2014. Data retrieval method performed with pre and post. Data collected by interviewing respondents via questionnaire. Leaflets are used as media to explain patients. There is a significant difference of patient’s knowledge before and after given explanation (p=0.002). Knowledge value of transtibial patients increased from 10% "Good" to be 80% "Good" after given explanation. Meanwhile, there is no significant relationship between age, gender and level of education to patient’s knowledge of maintaining the health of the stump.